Genetic and habitat variation among populations of the critically imperiled Vicia ocalensis (Fabaceae) in the Ocala National Forest, USA - Oleas, Nora (2018)
Vicia ocalensis Godfrey & Kral (Ocala vetch) is a declining endemic plant that is state-listed as endangered in Florida and as critically imperiled globally. This perennial vine is historically known from only three populations along the shorelines of separate spring systems within the Ocala National Forest. One of these populations recently rejuvenated after being absent for 15 years. All populations have experienced great annual fluctuations in size, and are increasingly threatened by recreational use of the springs, herbicide treatment, and other habitat disturbances. The aims of this study are to assess genetic diversity within and between the three historical populations of V. ocalensis and characterize habitat supporting the two extant populations of V. ocalensis to inform conservation strategies. We analyzed 743 amplified fragment length polymorphism (AFLP) markers. Our AFLP results show evidence of high inbreeding and weak genetic differentiation among populations. Genetic diversity within Population 1 and Population 3 was lower than Population 2. Complementary monitoring data over the last 10 yr shows population size declines in these three populations. The low genetic diversity and inbreeding is a concern for this species, especially coupled with habitat loss, degradation, and fragmentation. Our analysis of habitat suggests that germination substrate is a key component in determining suitable habitat for V. ocalensis, but understory and overstory plants may also influence habitat suitability. Habitat protection, restoration of similar habitats, population introductions, and ex situ preservation are all recommended for this species. © Copyright 2018 by The Torrey Botanical Society.